Pengaruh Kerja Sama Indonesia dan Filipina terhadap Penanggulangan Terorisme Tahun 2014 - 2017 - Iqlillah Febriana (Universitas Sains dan Teknologi Komputer, 2023)
Indonesia and the Philippines are members of ASEAN, both founders of ASEAN. If we look at geographical conditions, both have potential in the agricultural sector. Thus, it is highly vulnerable to acts of terrorism from both sides such as terrorist threats, money laundering and so on. This study will analyze the effect of Indonesia's cooperation with the Philippines in 2014 - 2017. The research method used in this study is qualitative descriptive with case study data collection techniques in this study, the author uses deterence theory. The results showed that there are 3 points on which it is based, namely: a) There is an increase in the ability and capacity of military and police personnel and security forces of each country. This proves that the relative theory (deterrence) is correct; b) There are fewer crimes and threats of terrorism in both countries than in previous years; c) The existence of dependence between the Philippines and Indonesia in carrying out relations between countries. This can be seen from the continued cooperation relationship.